Manufacture of Solar Panel with 300W Inverter for Household Electricity Needs - Yanatra Budi Pramana; Akhmad Solikin; Akhmad Faisal; Djoko Adi Walujo; Rusdiyantoro; Manik Ayu Titisari (Tibuana, 2022)
Solar panels are semiconductor elements that can convert solar energy into electrical energy. This Research on Solar Power Plants (PLTS) assemble with materials such as solar panels, 3000 W inverters, batteries, relays and control chargers, after that the load calculations are carried out, then implementation and testing is carried out. This research also aims as a renewable electric power in the future. From the results of the PLTS load test carried out at the researcher's house, the highest load was 405.32 watts, while the highest load test results used PLN electricity, which was 267.06 watts. So it can be said that this research is successful in meeting the electricity needs of household scale.